Composition and structure of composite coatings based on metal oxides and polytetrafluoroethylenedeposited under conditions of electron-initiated endothermic processes; Eurasian Physical Technical Journal; Vol. 17, No. 2 (34) - Surzhikov A. P. Anatoly Petrovich; Chicherina N. V. Natality Viktorovna; Rogachev A. V. Aleksandr Vladimirovich; Yarmolenko M. A. Maksim Anatoljevich; Rudenkov A. S. Aleksandr; Rogachev A. A.; Jicheng W. (2020, 2020)
Title screen